Residual Iterative Method for Solving Absolute Value Equations - Muhammad Aslam Noor; Javed Iqbal; Eisa Al-Said (Abstract and Applied Analysis)
We suggest and analyze a residual iterative method for solving absolute value equations Ax-x=b where A∈Rn×n, b∈Rn are given and x∈Rn is unknown, using the projection technique. We also discuss the convergence of the proposed method. Several examples are given to illustrate the implementation and efficiency of the method. Comparison with other methods is also given. Results proved in this paper may stimulate further research in this fascinating field.